BEBERAPA ASPEK GEOMETRIKA JALAN HUTAN DAN HUBUNGANNYA DENGAN EROSI TANAH - Djaban Tinambunan (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
A study on the forest road geometrics in relation to the process of soil erosion was carried out at four logging companies in Kotawaringin Timur, Central Kalimantan in 1988. Road geometric aspects measured in the field are those related to the Universal Soil Loss Equation factors such as road openings, surfaces, slopes, ditches, culverts, cuts, fills,diversion ditches, and the incidence of vegetation.The result shows that forest road geometrics are in the condition of high potentials for soil erosion. Factors that caused this problem, as identified in the field, are: long and steep slopes, wide ground openings, and bare soil surfaces, in addition to the originally sensitive to erosion soil type, an.d hot and wet weather.The concessionaires and Indonesian Government have not given proper attention to the seriousness of this soilerosion yet. Qualitatively we know that the erosion level is high but quantitatively we do not know the value yet. Therefore, further study is necessary.